Organizing for Pricing - Martin Jarmatz (Copenhagen Business School (CBS), 2018)
Pricing is the number one driver of profitability (Hinterhuber, 2004) and deserves greater attention from practitioners and academics (Kienzler & Kowalkowski, 2017; LaPlaca, 1997; Liozu, 2015). Research on pricing processes in business-to-business contexts is still underdeveloped (Leone, Robinson, Bragge, & Somervuori, 2012; Rao & Kartono, 2009). In line with authors, such as Homburg, Jensen, and Hahn (2012) and Liozu and Hinterhuber (2017), Carricano, Trinqueste and Mondejar (2010) particularly stress that there is a "continued lack of research providing sufficient detail to understand how companies organize for pricing" (p. 468). It is important to shed light on the phenomenon of organizing in terms of pricing to better understand firms' internal pricing processes and how they arrive at prices, to eventually help firms to move towards smarter pricing and potentially higher profitability (Carricano et al., 2010; Liozu, 2015). Based on this foundation and motivation, this dissertation addresses the following research question: how do firms organize for pricing? For this purpose, an organizing perspective is applied. Rather than focusing on the static aspects of the pricing organization, it draws attention to the process of organizing. Hence, it is a process lens that acknowledges dynamic ways of understanding social phenomena in organizations (Langley & Tsoukas, 2010).
hdl:10398/9634
Keywords: 650